Alkali treatment on nettle fibers part II: design of experiment and desirability function approach to study enhancement of tensile properties. Issue 8 (3rd August 2017) - Kumar, Navdeep; Das, Dipayan
Abstract: In this work, an attempt was made to enhance the tensile properties of nettle fibers by alkali treatment. The role of alkali treatment in determining tensile strength, elongation-at-break, and initial modulus of nettle fibers was examined using a fractional factorial design of experiments. Alkali concentration, alkalization time, alkalization temperature, drying time, and drying temperature were found to play significant roles in deciding the tensile properties of nettle fibers. Simultaneous optimization of tensile properties was performed using desirability function approach. The optimum alkali treatment yielded about 30% improvement in tensile strength, 71% improvement in elongation-at-break, and 9% reduction in initial modulus as compared to those of untreated nettle fibers.